Do plants freeze upon uncertainty shocks? - Ariel Mecikovsky; Matthias Meier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Following the real option literature, whether or not uncertainty shocks drive business cycles depends on the degree of adjustment frictions. The more plants freeze and remain inactive in response to increased uncertainty, the stronger the adverse effects on the economic activity. Using quarterly labor flow data of U.S. establishments, we find that an unexpected increase in uncertainty reduces hiring, quits and job creation, while it raises layoffs and job destruction. Our finding suggests that plants remain active as a result of uncertainty shocks. A partial equilibrium model with capital and labor adjustment costs can not explain our empirical results. Surprise increases in uncertainty leads plants to freeze investment and labor policies. We are able to rationalize our findings using a version of this model without labor adjustment frictions. As uncertainty increases, more plants adopt a wait-and-see policy for investment. This, in turn, reduces capital through depreciation of the existing capital stock, and thereby lowers labor demand, which implies more layoffs and less hiring. The model implies that economies with flexible labor market regulations should experience more layoffs and job destruction upon an uncertainty shock with respect to economies with stricter regulations. Using additional labor ow data from Germany, France and UK, we obtain empirical evidence that supports this hypothesis.
Keywords: J23; J63; D81; 330; Uncertainty; real-option; labor demand; Risk; Real options analysis; Labour demand